Phenolic profiling of selected herbal plants: free, soluble bound and insoluble bound phenolics and their antioxidant activities - Mohd Yusof, Nor Amaliana Syazwani; Haron, Normah; Mat Jusoh, Hanapi (Society of Education, India, 2019)
This study was conducted to profile selected phenolic acids, total phenolic content and antioxidant activities of five herbal plants namely Citrus hystrix, Coriandrum sativum, Murraya koenigii, Polygonum minus and ocimum basilicum in three different phenolic fractions (free, soluble bound and insoluble bound). The phenolic content was quantified using Folin-Ciocalteu method and phenolic acids were separated using C6-phenyl column High Performance Liquid chromatography. The antioxidant properties were determined using DPPH (2, 2-Diphenyl-1-picrylhydrazyl) and ABTS (2,2’-Azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)) assays. The result showed that gallic, caffeic, ferulic, sinapinic and p-coumaric acids were detected in distinctive proportion. Bound forms of phenolic acids (soluble and insoluble bound) have high phenolic contents as compared to free phenolic. P. minus and O. basilicum demonstrated higher total phenolic content and showed promising antioxidant activities .The antioxidant properties can be correlated with the presence of phenolic acids in the extracts. To conclude, the herbal plants have the potential in reducing ability due to their strong electron-donating effects.